DIGITAL RESOURCE TO STUDY MATHEMATICS AND MANAGE THE LEARNING PROCESS OF STUDENTS BY KHAN ACADEMY - Mardenova , L.K.; Maksat А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This article shortly researches how does it work: one of the popular free online platforms called Khan Academy to study Mathematics in the perspective of methodology of teaching. Khan Academy is free online platform with video tutorials and explanations with exercise dashboard for learning subjects like Mathematics, Science and more. This digital resource provides statistics for teachers to monitor the progress of students. In this article written explanations why it is effective and how it could be implemented to Kazakhstan’s schools. The method of research is observing the experiences of overseas schools by analyzing articles and additionally made a personal observation of the platform. Schools in the American continent use flipped classes with Khan Academy to learn Mathematics inside and outside of the class effectively for non-cost. This idea of flipped class for mathematics would be efficient in Kazakhstani schools for secondary school students and also for students who are preparing for taking National Common Test for entrance to university.